Evaluation of the Fourth Grade Mathematics Textbook in Algerian Schools in Light of Total Quality Standards from the Perspective of Primary School Teachers - Chehilita, hacene; labouz, abdellah (Journal of Social Sciences and Humanities, 2024)
The aim of this study is to evaluate the content of the fourth-grade mathematics textbook in Algeria according to comprehensive quality standards, from the perspective of primary school teachers, within the framework of the second generation of reforms, which was implemented in the 2016/2017 academic year. The descriptive approach was used due to its suitability to the nature and objectives of the study. The tool was applied to a randomly selected sample consisting of fifty-eight (58) primary school teachers. The study findings revealed the following: The comprehensive quality standards that should be present in the fourth-grade mathematics textbook include: general format, educational objectives, content, language, and evaluative activities. The content of the fourth-grade mathematics textbook in Algeria meets most of the comprehensive quality standards and is considered to be at an acceptable level according to the teachers' assessments, as follows: The general format of the textbook scored highest among the five domains with 75%. Educational objectives: 70%.Language: 68%.Educational content: 66%.Evaluative activities: 64% of teachers believe it meets comprehensive quality standards. The study resulted in the development of an evaluation tool based on comprehensive quality standards, which can be used to assess the fourth-grade mathematics textbook. There are no significant differences in the average teacher evaluations of the mathematics textbook's quality based on gender. There are significant differences in the average teacher evaluations of the mathematics textbook's quality based on teaching experience. Keywords: Evaluation, Textbook, Comprehensive Quality Standards. The aim of this study is to evaluate the content of the fourth-grade mathematics textbook in Algeria according to comprehensive quality standards, from the perspective of primary school teachers, within the framework of the second generation of reforms, which was implemented in the 2016/2017 academic year. The descriptive approach was used due to its suitability to the nature and objectives of the study. The tool was applied to a randomly selected sample consisting of fifty-eight (58) primary school teachers. The study findings revealed the following: The comprehensive quality standards that should be present in the fourth-grade mathematics textbook include: general format, educational objectives, content, language, and evaluative activities. The content of the fourth-grade mathematics textbook in Algeria meets most of the comprehensive quality standards and is considered to be at an acceptable level according to the teachers' assessments, as follows: The general format of the textbook scored highest among the five domains with 75%. Educational objectives: 70%.Language: 68%.Educational content: 66%.Evaluative activities: 64% of teachers believe it meets comprehensive quality standards. The study resulted in the development of an evaluation tool based on comprehensive quality standards, which can be used to assess the fourth-grade mathematics textbook. There are no significant differences in the average teacher evaluations of the mathematics textbook's quality based on gender. There are significant differences in the average teacher evaluations of the mathematics textbook's quality based on teaching experience.